Load-bearing ORIF of mandibular fracture caused by firearms projectiles: Case series. (October 2021) - Silva, A.; Costa, S.; Campos Ribeiro, B.; Figueiredo Amaral, M.; Goncalves, A.
Abstract : Purpose: The main challenge in mandibular fractures caused by firearms is restore the anatomy in the fracture areas, due to the severe destruction of the bone and tooth borne structures. To reestablish these areas, load sharing devices usually lacks support, leading to non-union and infections. Strong systems, with load-bearing pattern are the gold-standard for the treatment of complex mandibular fractures. Methods: A series of patients with mandibular fracture caused by firearms injuries was treated with load-bearing devices and followed to observe the complications and outcomes. Results: A total of 22 patients were enrolled by this study, 19 male and 3 females. All the patients were treated with transcutaneous approach and rigid fixation with a 2.4 mm titanium plate, a total load-bearing device. The complication rate was considered low, with infection of the surgical site (13%) and material fatigue (9%) the most prevalent. Conclusion: Open reduction and internal fixation of mandibular fractures with load-bearing devices is a reliable procedure. The use of these materials in cases of caused by firearms projectiles is fundamental to promote the correct for bone support in long term.